Improvement of the enterprise human resources management system based on hr-analytics - Li,Xiaojing (Харківський національний автомобільно-дорожній університет, 2024)
The relevance of the research topic is that the role of analytics in an organization is growing due to the rapid development of the Internet, machine learning, and artificial intelligence. The main way to use large amounts of data is to use HR analytics tools. The study used both theoretical methods (study of literature sources, analysis, description, generalization, classification) and empirical methods (interviewing, questionnaires, data collection, performance analysis). The paper considers the theoretical aspects of HR analytics and data about people; analyzes the effectiveness of HR analytics in LLC «EAST-TEL»; offers practical recommendations for the implementation of the HR analytics system in LLC «EAST-TEL».
Keywords: hr-analytics management; enterprise personnel; motivation; personnel management system